Resíduo da semente de maracujá na alimentação de frangos de corte e poedeiras comerciais - Zanetti, Leonardo Henrique (2015)
Three experiments were conducted to determine the nutritional value of passion fruit seed residue (PFSR) in feeding of broilers and commercial chickens. Experiment I - 72 Cobb male broilers at 21 days of age were used in metabolism cages in a completely randomized design with two treatments, six replicates and six birds each. To determine the energy value and the composition of passion fruit seed residue we used the method of total excreta collection. The treatments were: basal diet and diet with 20% of passion fruit seed residue substitution. The energy of the residue was 3,954 kcal of AME/kg and 3,945 kcal of AMEn/kg. Experiment II - 864 Cobb male broilers were created from 1 to 42 days of age in a completely randomized design with six treatments (control, 2.5%, 5.0%, 7.5%, 10.0% and 12.5% inclusion of PFSR), and six replicates of 24 birds each. The inclusion of PFSR in the diets of broilers from 1 to 21 and 1 to 42 days linearly worsened (P<0.05) feed conversion, and did not affect weight gain, feed intake, and carcass or cuts yield. At 21 days of age, there was no effect on blood cholesterol, however triglyceride levels decreased (P<0.05) and at 42 days of age no effects were observed for these variables. The relative weights of the gastrointestinal tract organs were not affected (P>0.05) by levels of PFSR inclusion at 21 days, and at 42 days of age a quadratic response (P<0.05) was observed only for relative liver weight. There was no difference (P>0.05) for villous height, crypt depth and villous:crypt ratio at duodenum and jejunum for 21 days. At 42 days there was effect (P<0.05) only for the characteristics evaluated in the jejunum, presenting linear decreasing to villous height. At 42 days of age there were no effects (P>0.05) on carcass yield, cuts and abdominal fat. For quality of breast, there was no difference (P>0.05), only the thigh showed a quadratic effect as for the red / green color. As for economic viability, levels above 5.0% inclusion of PFSR proved to be economically viable. Experiment III - 384 commercial chickens from a commercial line Hy-line W36 at 30 weeks of age were distributed in a completely randomized design, with six treatments (control, 2.5%, 5.0%, 7.5%, 10% and 12.5% inclusion of PFSR), eight replicates and six birds each. The productive performance was evaluated for three cycles of 28 days each. The egg quality was evaluated in the last four days of each cycle. There were no differences (P>0.05) for percentage of egg production and feed conversion (kg kg-1 e kg dz-1). However the feed intake showed a positive linear response (P<0.05). The egg weight, egg mass, percentage, egg shell thickness and Haugh unit did not differ (P>0.05) with increasing levels of PFSR inclusion. However, the specific gravity of eggs improved (P<0.05) with PFSR addition. The total cholesterol and triglycerides linearly decreased (P<0.05). PFSR can be added to the diet of laying up to 7.5%, without compromising performance parameters and up to 12.5% on quality of eggs. As for economic viability, levels above 10.0% of PFSR inclusion proved to be economically viable.